A Builder of Bridges Between the Cultures and Religions (rwth-aachen, 2015)
In a festive ceremony, the German Ambassador to Oman, Hans-Christian Freiherr von Reibnitz, presented the honor to His Excellency Sheikh Abdullah bin Mohammed Al Salmi in the presence of high-profile guests from politics, business, and academia, including H.H. Sayyid Haitham Bin Tariq Al Said, Minister of Heritage and Culture, H.E. Dr. Rawiyah Al Busaidiyah, Minister of Higher Education, and H.E. Yusuf Bin Alawi, Minister of Foreign Affairs.
Keywords: Relations – Oman – Allemagne